1968
DOI: 10.1080/00288330.1968.9515260
|View full text |Cite
|
Sign up to set email alerts
|

Stages in the normal development of Galaxias maculatus attenuatus (Jenyns)

Abstract: The sequence of embryonic development is described for Galaxias maculatus attenuatus (Jenyns). Standard stages are described and the rate of development at two different constant temperatures is given. Field results are compared with these data. It appears that G. m. attenuatus is very temperature labile in its development, an adaptation of high survival value in the habitat in which the eggs are laid

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
8

Year Published

1991
1991
2013
2013

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(55 citation statements)
references
References 3 publications
0
45
0
8
Order By: Relevance
“…McDowall et al (1994) found similar durations for the first life stages when they found that G. maculatus lived at sea (free embryo and larval periods) for 103-202 days. The different adult, egg, and free embryo size of landlocked (Pollard 1971;Cussac et al 1992;Cervellini et al 1993) and diadromous populations (Benzie 1968) and probably slower larval growth rate in fresh water could be partly attributed to the scarce food resources available in oligotrophic lakes. Particularly, low food availability in the limnetic zone may be the cause of the smaller maximum metamorphic size in landlocked populations (28 mm SL), as compared with diadromous populations (>35 mm SL, McDowall et al 1994).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…McDowall et al (1994) found similar durations for the first life stages when they found that G. maculatus lived at sea (free embryo and larval periods) for 103-202 days. The different adult, egg, and free embryo size of landlocked (Pollard 1971;Cussac et al 1992;Cervellini et al 1993) and diadromous populations (Benzie 1968) and probably slower larval growth rate in fresh water could be partly attributed to the scarce food resources available in oligotrophic lakes. Particularly, low food availability in the limnetic zone may be the cause of the smaller maximum metamorphic size in landlocked populations (28 mm SL), as compared with diadromous populations (>35 mm SL, McDowall et al 1994).…”
Section: Discussionmentioning
confidence: 99%
“…G. maculatus and G. platei both have indirect ontogeny (Benzie 1968;McDowall 1968;Ortubay & Wegrzyn 1991). There is little information about the larvae of most Galaxiidae (Campos 1972;Hopkins 1979;McDowall & Suren 1995), mainly because of their marine habitat (McDowall et al 1994).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…From observations of mature to ripe fish in the adult populations, it has been conjectured that spawning takes place in autumn and early winter (McDowall 1990);and back-M94053 Received 20 October 1994;accepted 3 February 1995 calculation from date of capture, using otolith daily growth rings (McDowall et al 1994), indicated that hatching of whitebait returning from the sea had taken place between mid April and early June. A spawning date about 3-4 weeks earlier than that seems likely, on the basis of development time in other galaxiids (Benzie 1968a(Benzie , 1968bMcDowall 1968;Mitchell & Penlington 1982). Spawning has been observed in an Australian population of koaro (Koehn & O'Connor 1992) during May-June, but has never been observed in New Zealand.…”
Section: Introductionmentioning
confidence: 99%